Peran Financial Literacy dalam Menjembatani Hubungan Antara Persepsi Risiko, Overconfidence dan Sosial Media Terhadap Keputusan Investasi Mahasiswa - Marta Erin Anggraini; Diana Puspitasari; Rudi Kurniawan; Almira Santi Samasta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the influence of risk perception, overconfidence, and social media on students' investment decisions, with financial literacy as a mediating variable. Using a quantitative explanatory method, primary data were collected through a courage questionnaire from students who have experience or basic knowledge of investing. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for analysis. The results showed that risk perception, overconfidence, and social media had a positive and significant impact on students' investment decisions. Financial literacy was also shown to have a positive and significant influence on investment decisions and was able to mediate the influence of the three variables. These findings reinforce the importance of financial literacy in helping students manage behavioral biases and filter digital information, thus enabling more rational and targeted investment decision-making. This research contributes to the development of behavioral finance studies in the context of student investment behavior in the digital era.